PROFIL STATUS GIZI PETANI DI JENEPONTO, SULAWESI SELATAN - Dadang Sukandar (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2007)
NUTRITIONAL STATUS PROFILE OF FARMERS IN JENEPONTO, SOUTH SULAWESI.Background: Social-economic and nutritional status of farmers in coastal area are still big problem in Jeneponto district. Special Program for Food Security (SPFS) under Food and Agriculture Organization has been being Implemented since 2000 to overcome the problems. Objectives: 1) to asses socio-economic, 2) to esess nutritional status of community and 3) to improve nutritional knowledge of farmers on food, nutrition, sanitation and hygiene through conducting training. Methods: Study was conducted in Jeneponto, South Sulawesi, from December 1995 to November 2006. A sample of size 45 households was drawn randomly from household population of size 226. The households population is household farmer who are beneficiary of Special Program for Food Secutity, Food and Acgrlculture Organization. Data were analyzed quantitatively and qualitatively and presented in table. Results: Reseacrh results show that level of income of farmer is medium level. Average income of farmer is about Rp 229,658 per capita per month. As much as 47% of expenditure was spent for food. There are still many husbund-wive who have nutrition problem. As much as 16 % of husbands are thin and 16% are overweight. As much as 20% wive are thin and 18 % are overweight. Conclusions: Average income of farmer is medium level. Almost 50 % of expenditure was spent for food. There are still many husband-wive who are thin and overweight. After attending training, knowledge on nutrition and food of the farmers increase significantly. Recommendation: Agriculture and Health office of the Jeneponto district need to continue the SPFS' project to increase farmers income and to improve nutritional status of the farmers.Keywords: socio-economic, food, nutrition, sanitation, hygiene.